2021
DOI: 10.1242/jeb.236505
|View full text |Cite
|
Sign up to set email alerts
|

Responses ofManduca sextalarvae to heat waves

Abstract: Climate change is increasing the frequency of heat waves and other extreme weather events experienced by organisms. How does the number and developmental timing of heat waves affect survival, growth and development of insects? Do heat waves early in development alter performance later in development? We addressed these questions using experimental heat waves with larvae of the Tobacco Hornworm, Manduca sexta. The experiments used diurnally fluctuating temperature treatments differing in the number (0-3) and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 53 publications
0
19
1
Order By: Relevance
“…Interestingly, the parasitoid appears to be resilient to heat waves during the intermediate portion of its larval development; while host mortality was increased in our Middle heat wave treatment, the surviving hosts produced parasitoids with comparable survival, development time, and adult mass to controls that never experienced a heat wave. The M. sexta hosts themselves could be sensitive to high temperatures during this developmental stage (Kingsolver et al, 2021), but this remains to be fully explored in parasitized caterpillars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the parasitoid appears to be resilient to heat waves during the intermediate portion of its larval development; while host mortality was increased in our Middle heat wave treatment, the surviving hosts produced parasitoids with comparable survival, development time, and adult mass to controls that never experienced a heat wave. The M. sexta hosts themselves could be sensitive to high temperatures during this developmental stage (Kingsolver et al, 2021), but this remains to be fully explored in parasitized caterpillars.…”
Section: Discussionmentioning
confidence: 99%
“…The heat wave regime was the same for all treatments: three days at 31 ± 11°C (daily maximum of 42°C for 2 h) (Figure 1a). Recent work has shown that a single exposure to this heat wave regime does not reduce survival, development time, or pupal mass of unparasitized M. sexta regardless of developmental stage (Kingsolver et al, 2021). The treatments differed in the developmental stage of the parasitoid larvae at which they experienced the heat wave temperatures (recall that caterpillars in all treatments were parasitized).…”
Section: Developmental Timing Heat Wave Experimentsmentioning
confidence: 99%
“…In fact, some studies have shown that using constant temperature conditions to explore the performance thermal response of insects may not reflect the thermal responses of insects under real field conditions because they do not mimic the fluctuating temperature conditions that occur within the natural environment. 1,31,36,37 The predaceous ladybeetle Propylaea japonica (Coleoptera: Coccinellidae) is a predominant coccinellid in South-East Asia, including China, South Korea, Japan, and India. 38 Propylaea japonica feeds on a variety of aphids and small insect species, and prevails in cotton, wheat, and corn fields.…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies have shown that high temperatures affect the performance of insects, the experiments are based on either constant high temperatures or short‐time exposures to high temperatures, and thus the studies may not adequately reflect the variable temperature conditions experienced in the natural environment. In fact, some studies have shown that using constant temperature conditions to explore the performance thermal response of insects may not reflect the thermal responses of insects under real field conditions because they do not mimic the fluctuating temperature conditions that occur within the natural environment 1,31,36,37 …”
Section: Introductionmentioning
confidence: 99%
“…Heat treatment has been widely used as a non-chemical disinfestation measure for postharvest crops (e.g., Cowley et al 1992;Waddell et al 1993;Jessup et al 1998;Jacobi et al 2001;Macana & Baik 2018). In invertebrates, particularly insects and mites, response to high temperature and exposure duration varies among species (Bertelsmeier et al 2015;Gray 2017;Kingsolver et al 2021) as well as among life stages within species (Heather et al 2002;Kingsolver et al 2011;Gotoh et al 2013;Chiu et al 2014;Hsu et al 2018;Yao et al 2019). Therefore, the effectiveness of heat disinfestation treatment should be determined by temperature, treatment duration (Dentener et al 1997;Lurie et al 1998;Finkelman et al 2006;Hara 2013) and life stages treated (Heard et al 1992;Heather et al 2002;Gotoh et al 2013;Hsu et al 2018).…”
Section: Introductionmentioning
confidence: 99%